Uniform equicontinuity for sequences of homomorphisms into the ring of measurable operators - Litvinov, S. N.; Chilin, V. I. (Methods of Functional Analysis and Topology, 2006)
We introduce a notion of uniform equicontinuity for sequences of functions with the values in the space of measurable operators. Then we show that all the implications of the classical Banach Principle on the almost everywhere convergence of sequences of linear operators remain valid in a non-commutative setting.